Decoding Consumer Choice: An Economic Analysis of Product Availability and Brand Awareness at PT Kurniaputra Mandiri - Situmorang, Irvan Rolyesh; Angkasa, Jesselyn; Setyorini, Dian (Yayasan Riset dan Pengembangan Intelektual, 2025)
In today’s highly competitive market, companies are increasingly focused on building a strong, customer-centric organizational culture while emphasizing social responsibility and sustainability. Despite these efforts, modern business management still faces challenges such as insufficient employee competencies, complex risk management, and the ongoing struggle to balance short-term performance with long-term strategic goals. This study aims to examine the effect of product availability and brand awareness on consumer purchase decisions at PT KurniaPutra Mandiri. A quantitative research approach was employed, involving a population of 129 consumers who purchased Honda motorcycles more than once in 2023. Based on the Slovin formula, a sample of 98 respondents was selected using an accidental sampling technique. The results indicate that product availability has a significant positive effect on purchase decisions. Similarly, brand awareness also positively and significantly influences purchase decisions. Furthermore, the study confirms that both product availability and brand awareness simultaneously have a significant impact on consumer purchase decisions at PT KurniaPutra Mandiri.